Diagnóstico de lesões de cárie oclusais iniciais em molares decíduos por padrão de espalhamento de luz coerente speckle - Olivan, Silvia Regina Garcia (2015)
The detection of incipient lesions of occlusal caries is a difficult task that requires a rigorous examination is commonly used visual and radiographic inspection. Tooth caries induce the mineral loss, alters the optical properties of the affected tissue, so the study of these properties can produce non-invasive and non-destructive methods for early diagnosis of caries lesions. Thus, the objective of this project is to correlate the results obtained by visual examination by ICDAS and the method by coherent light scattering speckle pattern (statistical patterns of optical granules (speckle) generated by sound and injured dental tissues) . Therefore, we used 30 healthy deciduous molar teeth coming from the Biobank Human Teeth, Faculty of Dentistry, University of São Paulo who had carious lesions induced by pH cycling method. The samples were evaluated for making the diagnosis of caries by two methods: ICDAS and speckle pattern of coherent light scattering in the periods after 5, 10 and 15 days and the results statistically analyzed using α = 0.05 significance level .It was observed a significant difference between the image of the speckle scattering of healthy and injured areas within the 3 study groups, but not when comparing the three groups, showing us that it is an innovative technique that needs further study, but it can be used as a diagnostic method for the detection of early caries lesions.